Physical activity and risk of workplace and commuting injuries : a cohort study - Alhainen, Maria; Härmä, Mikko; Pentti, Jaana; Ervasti, Jenni; Kivimäki, Mika; Vahtera, Jussi; Stenholm, Sari (Nordic Association of Occupational Safety and Health NOROSH, 2025)
Objective: Leisure-time physical activity (PA) has been hypothesized to reduce the likelihood of occupational injuries, but it is unclear whether this association varies between workplace and commuting injuries. The aim of this study was to examine the association between PA and risk of workplace and commuting injuries.
Methods: Data were derived from the Finnish Public Sector study including 82 716 person-observations (48 116 participants). PA was requested repeatedly in four questionnaire surveys between 2000-2012. The average level of PA from two subsequent questionnaires was used to assess long-term PA. To obtain a 1-year incidence of injuries, participants were linked to occupational injury records from the national register. Logistic regression analysis with generalized estimating equations was used to examine the association between PA and injury risk. The analysis was adjusted for age, sex, education, work schedule, job demand, sleep difficulties, cardiovascular diseases, diabetes, and depression for workplace and commuting injuries, and workplace injuries were additionally adjusted for physical heaviness of an occupation and injury risk by occupation.
Results: Higher level of PA was associated with a lower risk of workplace injuries compared to inactive participants [odds ratio (OR) 0.85, 95% confidence interval (CI) 0.73-0.98]. This association was most marked in the ≥50-year-old age group (OR 0.78, 95% CI 0.64-0.99). No association between the PA and the risk for commuting injuries was observed.
Conclusion: Higher PA is associated with lower risk of workplace injuries particularly among older employees.